Efeitos do treinamento físico agudo e crônico sobre o transporte cólico de água e eletrólitos em ratos anestesiados - Rocha, Francisco Socorro (2014)
Introduction : The physical exercise (PE) promotes effects on the gastrointestinal tract that can have negative or positive impact on the individual and may lead to hemodynamic changes and motility already established , however the repercussions of this on the colonic transport of water and electrolytes yet is not established. Objective: To evaluate the effect of PE on chronic and acute colonic transport (CT) of water and electrolytes. Methods: Wistar rats ~ 250 - 400g; (chronic group, N = 77) and weighing ~ 180 - 250g; (acute group, N = 133), coming from the animal house of the college of Medicine-Sobral, who underwent the following training protocols were used : acute training consisted of 5 days (d) consecutive swimming collective. In the 48 hours after the last session we held an individual workout 15min with 5 % of body weight , Already aerobic training took place in a session of 60min/d under 5d/week over 12 weeks in a tank at ~ 31 o C. Anaerobic activity consisted of 4 sets of 10 jumps, daily for 12 week. In the initial 4 week employ 50% of body weight, an increase of 60%, 70% and 80% every 4 week. For the colic perfusion procedure animals remained on fasting for 48h , with free access to Oral rehydration solution (ORS) and then underwent the following experimental protocols: effect of chronic exercise training aerobic and anaerobic on colic transport of water and electrolytes, envolviment of parasympathetic neural pathways on colic transport from the acute exercise: bilateral cervical vagotomy; subdiaphragmatic truncal vagotomy, atropine (0,5 mg/kg, sc), envolviment of sympathetic neural pathways: esplancnotomia; guanethidine (10 mg/kg, sc); envolviment of the NO Synthase/K + ATP– dependent channels: L-NAME (10mg/kg , sc) and glibenclamide (1mg/kg, sc). envolviment of soluble guanylate cyclase/cGMP pathway: methylene blue (Blue) (3mg/kg , s.c). After 40 min the animals were anesthetized (Ketamine/Xylazine 20-10mg/Kg-IP ), followed by laparotomy with implantation of polyvinyl cannulas (OE=50mm/OI= 30mm). The colon was perfused (0.16mL/min-Tyrode, 0,05mg/mL phenol red (VF) at 37oC/60min ). Variations in the concentrations of Na+, K+, Cl-, Ca++, HC03- (mmol/L- selective Ion) and VF were used to determine the TC. Test data were analyzed by Student "t" (P < 0,05). Results: Chronic EF promoted secretion (P < 0.05) colic H2O, Na+, Cl-, K+, but did not affect the Ca++ and HC03- as compared to the sedentary (absorption). Already EF acute in vagotomized animals, or pretreated with atropine showed decreased secretory pattern or absorption. Likewise the splanchnotomy or pretreated with guanethidine animals showed absorption. Since the pretreatment with L-NAME, Blue and glibenclamimide led to a decrease in the secretory pattern or absorption. Conclusion: The results suggest that EF is able to promote secretion of water and electrolytes by a mechanism dependent on the parasympathetic and sympathetic pathways or the NO/Synthase/GC/K+ ATP-dependent channels pathway.